Fabrication of Hollow Microspheres Using Single Step Electrospraying Process - Ramamurthy, Praveen C.; Khadija, K. K.; Ranjith, K.; Mishra, Sumeet R. (Journal of Research Updates in Polymer Science, 2014)
In this study, a single step method for large scale fabrication of hollow microspheres with a narrow size distribution is presented. PolyBenzoThiadiazole (PolyBT), a conducting polymer, was electrosprayed at high voltage to obtain microspheres. Hollow spheres of size ranging from 4.1 to 7.3 µm were observed through scanning electron microscope images, without any chemical degradation as shown by FTIR studies. In addition, these microspheres demonstrated a change in optical and hydrophobic properties as exhibited by the UV-visible and contact angle measurements. Thus providing interesting opportunities for use in biomedical applications, sensors as well as optoelectronic devices.